Evaluation of the Validation Process of Prospective Recipients of Educational Scholarships on the Siaplah Platform: A Case Study at The West Kalimantan Provincial Education and Culture Office - Firman Cahyadi; Nur Aini Rakhmawati (Publikasi Indonesia, 2024)
This study aims to evaluate the validation process of prospective recipients of educational scholarships through the Siaplah platform implemented by the West Kalimantan Education and Culture Office. The research methods used in this study are Business Process Improvement (BPI) and Failure Mode and Effects Analysis (FMEA). Because BPI can evaluate in aligning processes with organizational goals and strategies. In the context of this research, BPI can assist the West Kalimantan Education and Culture Office to ensure that the scholarship validation process supports the achievement of organizational goals related to education. Meanwhile, FMEA is used to identify potential risks, failures, and weaknesses in the validation process. Through this analysis, research can identify critical points in the process that could lead to failures or problems. So the FMEA can be improved by giving a score on each risk and impact. Research results: Business process recommendations for prospective PBP recipients are made based on the design of business process improvement that has been carried out using the Business Process Improvement (BPI) method. Some activities have changed, activities that have been added to activities that have been removed. From the results of simulations carried out on the current business process (as it is) and business process recommendations (to be), it was found that the increase in time analysis reached 02.8% in the business process of prospective PBP recipients, 1.44% in the implementation of the business of prospective PBP recipients, and 1.55% in the business evaluation of prospective PBP recipients.